Situation Report: Bulgaria, 12 May 1984 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. A Decree on the Standard of Living / by Rada Nikolaev Nuclear Power Projects and Cooperation with USSR / by Rada Nikolaev Educational Reform Puts Students to Work / by Deana Tosheff Handicapped Children and Social Services